Penerimaan Orang Tua Terhadap Keberadaan Anak Berkebutuhan Khusus di Lembaga PAUD - Reni Rulita; Shanti Hataul; Septiyani Endang Yunitasari; Umilia, Umilia (Student Journal of Early Childhood Education, 2023)
Children with special needs are children who have physical, intellectual, emotional, and social limitations that affect the child's development and growth processes compared to other children. Parents' attitudes and behaviors are very influential for the development of children with special needs because parental support provides a successful developmental process. This study aims to describe the forms, treatment, and factors of parental acceptance of the existence of children with special needs with literature review research methods from various literature reviews in reputable National journals. The results of the study showed various forms of parental acceptance of children with special needs in Early Childhood Education (PAUD) institutions.